Neurological and Neuropsychiatric Manifestations of Pediatric Inflammatory Multisystem Syndrome (PIMS/MIS-C): A Narrative Review - Wiktor Śliwiński; Weronika Pura; Dominika Matecka; Mateusz Kosowski; Daniel Chołuj; Jakub Marciniak; Jakub Mazur; Karolina Zarówna; Laavanya Damodaran; Natalia Szejko (Journal of Personalized Medicine, 2026)
Background: Pediatric inflammatory multisystem syndrome (PIMS), also referred to as multisystem inflammatory syndrome in children (MIS-C), is a rare but serious post-infectious complication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection characterized by systemic hyperinflammation and multiorgan involvement. New-onset neurological and psychiatric symptoms have emerged as critical clinical features, occurring in approximately 12–27% of pediatric patients aged 2–15 years (median age, 10 years) and often indicating a more severe disease course. This narrative review aims to provide a comprehensive overview of the current literature regarding the neurological and psychiatric manifestations of PIMS/MIS-C, focusing on epidemiology, pathophysiology, clinical presentation, neuroimaging findings, biomarkers, treatment strategies, and outcomes. Methods: A narrative literature review was conducted to synthesize current evidence on the neurological and psychiatric spectrum of PIMS/MIS-C. Evaluated parameters included clinical presentations ranging from common symptoms (such as headache, encephalopathy, altered mental status, and seizures) to rare complications (such as ischemic stroke, acute disseminated encephalomyelitis, Guillain–Barré syndrome, and cerebral edema), alongside associated psychiatric disturbances, diagnostic findings, and therapeutic approaches. Results: Neurological and psychiatric manifestations significantly impact the clinical trajectory of PIMS/MIS-C. Acute symptoms include headache, encephalopathy, seizures, and psychiatric disturbances like behavioral changes, hallucinations, delirium, anxiety, and sleep disorders. Neuroimaging in many cases reveals reversible lesions of the splenium of the corpus callosum, while electroencephalography typically demonstrates diffuse slowing consistent with encephalopathy. Early recognition and prompt administration of immunomodulatory therapy—primarily intravenous immunoglobulin and corticosteroids—correlate with favorable neurological recovery in the majority of patients. However, current evidence remains largely observational and heterogeneous, precluding definitive causal conclusions regarding this treatment–outcome relationship. Affected children more frequently require intensive care unit admission and remain at risk for persistent cognitive, behavioral, and psychiatric sequelae. Conclusions: Neurological and psychiatric complications in PIMS/MIS-C are clinically significant indicators of disease severity that require vigilant monitoring and early immunomodulatory intervention. Continued multidisciplinary follow-up and prospective studies are essential to elucidate the long-term neurodevelopmental and psychiatric consequences and to optimize therapeutic strategies for these patients.